1035325 Studi Deskriptif : Yoga Prenatal Terhadap Ketidaknyamanan yang dialami Ibu Hamil Trimester III di Yayasan Bumi Sehat Ubud-Bali, Indonesia - Ni Wayan Noviani; Ni Wayan Sukma Adnyani (STIKes Budi Mulia Sriwijaya, 2019)
Abstract During pregnancy, pregnant women will experience physiological and psychological changes. Changes in pregnancy may cause discomfort for the mother, especially in TM III. Prenatal yoga is an effective effort to reduce the discomfort experienced by pregnant women. The aim of this study is to identify prenatal yoga in reducing the discomforts of TM III pregnant women. This research is a descriptive study with cross-sectional design. The number of samples in this study were 50 pregnant women who met the inclusion criteria with a purposive sampling technique. The results were obtained based on the variable back pain most of the mothers did not feel significant back pain, most did not experience anxiety, most had a good resting pattern, physiological shortness of breath was reduced in TM III pregnant women and most did not experience cramps and swelling (physiology ) on the extremities. So it can be concluded that regular prenatal yoga can reduce discomfort TM III pregnant women. Keywords: Prenatal Yoga, Discomfort, Pregnant Women Trimester III